Psychosocial effects of community noise: cross sectional study of school children in urban center of Skopje, Macedonia - Ristovska, Gordana; Gjorgjev, Dragan; Pop Jordanova, Nada (University of Zagreb Medical School, 2004)
To assess noise exposure in school children in urban center in different residential areas and to examine psychosocial effects of chronic noise exposure in school children, taking into account their socioeconomic status.
Keywords: child development; noise; transportation; psychological tests; social class